78 Lameness Culling Risks and Relative Risk Ratios for Gilts and Sows on Commercial Farms. (10th April 2018) - Tani, S; Yatabe, Y; Piñeiro, C; Koketsu, Y
Abstract: The objectives of this retrospective swine cohort study were 1) to characterize culling risks and relative risk ratios for served females and farrowed sows culled due to lameness on commercial farms, and 2) to quantify the factors associated with these by-parity culling risks. Data from farm-entry to removal included 710, 740 first service records of 140, 763 females on 121 Spanish farms, served between 2011 and 2016. Two farm categories were defined on the basis of the upper 25 th percentile of the farm means of the number of pigs weaned per sow per year: high-performing farms (> 26.7 pigs) and ordinary farms (≤ 26.7 pigs). Then, mixed-effects models were applied to the by-parity and lifetime data. Nearly 5% (4.7%) of the 140, 763 removed females were culled due to lameness, with mean by-parity culling risks (± SEM) due to lameness for served females and farrowed sows being 0.24 ± 0.01 and 0.74 ± 0.01%, respectively. Also, the mean respective culling incidence rates due to lameness were 0.20 and 2.47 pigs per 100 pig-days. The higher lameness culling risk for served gilts was associated with being fed on high-performing farms (P < 0.05), but there was no association with gilt age at first-service (P=0.06). For served sows, by-parity culling risks due to lameness were not associated with lactation length (P ≥ 0.08) or farm productivity groups (P ≥ 0.28). However, higher culling risks for farrowed sows were associated with sows having 112 days or shorter gestation length, farrowing 3 or more stillborn piglets and being fed on high-performing farms (P < 0.05). The relative culling risk ratios were 1.56-2.01 for sows having 112 days or shorter gestation length, 1.47-2.26 for sows farrowing 3 or more stillborn piglets, and 2.23-2.63 for sows being fed on high-performing farms, compared with the respective reference sows having 113-117 days gestation length, farrowing no stillborn piglets and being fed on ordinary farms. In conclusion, in order to identify lameness at an early stage we recommend that producers closely monitor at-risk female pigs, such as sows having shorter gestation length or farrowing some stillborn piglets.